Progress in heterocyclic chemistry. Vol. 18, A critical review of the 2005 literature preceded by two chapters on current heterocyclic topics - Gribble, Gordon W.; Joule, J. A. (John Arthur) (Oxford ; Boston : Elsevier, 2007)
The eighteenth annual volume of Progress in Heterocyclic Chemistry, covers the literature published during 2005 on most of the important heterocyclic ring systems. This volume opens with two specialized reviews. The first, by Heui-Yeon Kim and Cheon-Gyu Cho covers 'The Diels-Alder cycloadditions of 3,5-dibromo-2-pyrone and its derivatives'. The second, by Jean-Luc Girardet and Stanley Lang discusses 'Recent developments in the chemistry of nucleosides'. The remaining chapters examine the 2005 literature on the common heterocycles in order of increasing ring size and the heteroatoms present. References are incorporated into the text using the journal codes adopted by Comprehensive Heterocyclic Chemistry, and are listed in full at the end of each chapter. Included in the index are systematic heterocyclic ring system names. * Includes new contributions from experts in the field * Covers literature published during 2005 on most of the important heterocyclic ring systems * Presents two specialized reviews.
1. The Diels-Alder cycloadditions of 3,5-dibromo-2-pyrone and its derivatives (Heui-Yeon Kim, Cheon-Gyu) 2. Recent developments in the chemistry of nucleosides (J.-L. Girardet, S. Lang) 3. Three-membered ring systems 4. Four-membered ring systems 5. Five-membered ring systems 6. Six-membered ring systems 7. Seven-membered rings 8. Eight-membered and larger rings.
Includes bibliographical references and index.
Keywords: Heterocyclic chemistry